Renaissance Theories of Vision. - Hendrix, John Shannon (Visual culture in early modernity., 2016)
How are processes of vision, perception, and sensation conceived in the Renaissance? How are those conceptions made manifest in the arts? The essays in this volume address these and similar questions to establish important theoretical and philosophical bases for artistic production in the Renaissance and beyond. The essays also attend to the views of historically significant writers from the ancient classical period to the eighteenth century, including Plato, Aristotle, Plotinus, St Augustine, Ibn Sina (Avicenna), Ibn al-Haytham (Alhazen), Ibn Sahl, Marsilio Ficino, Nicholas of Cusa, Leon Batt.